(untitled) (Research, Society and Development, 2021)
Objective: To describe the clinical aspects of Polycystic Ovary Syndrome (PCOS) and its impact on women’s health. Methodology: Integrative literature review using the Scientific Eletronic Library Online (SciELO), PUBMED and Latin American and Caribbean Literature (LILACS) databases. Results: The analysis of the clinical picture of PCOS was divided into five topics: influence of Insulin Resistance (IR); relationship with obesity; hyperandrogenism and hirsutism; Metabolic Syndrome (MS) and cardiovascular risk; and interference with sexual life. In this sense, the hyperglycemic state generated by IR determined the development of diabetes and acanthosis nigricans, while obesity was observed both as a consequence of PCOS and as an aggravating factor in the symptoms of this syndrome. In addition, the presence of MS was influenced by the Body Mass Index (BMI) and age. As for sexuality, studies have noted the occurrence of sexual dysfunction, due to physical changes and hormonal disorder, and infertility, due to non-ovulation. Conclusion: We conclude that PCOS generates a very heterogeneous range of symptoms, which manifest themselves in more than one phase of a woman’s life and, therefore, a holistic approach to the patient is necessary. In addition, healthy lifestyle habits, such as a balanced diet and exercise, positively influence the improvement of symptoms.